Privacy preserving lightweight authentication scheme for roaming service in global mobile networks - Sungwoon Lee; Hyunsung Kim (International Journal of Advances in Applied Sciences, 2024)
The swift advancement of mobile intelligent terminals and services enables users to seamlessly access ubiquitous services across global mobile networks. Ensuring the authentication and safeguarding of the privacy of network entities is crucial. Numerous authentication and privacy schemes have been put forth over time, yet many of them have faced security and privacy challenges. A recent contribution introduces a lightweight authentication scheme (LAS) designed for roaming services within global mobile networks. They assert that their scheme offers user anonymity, mutual authentication, fair key agreement, and user-friendliness, claiming resilience against various attacks in global mobile networks. This paper, however, identifies two design flaws in the LAS and highlights its vulnerability to two masquerading attacks and a mobile user (MU) trace attack. Consequently, we propose a privacy-preserving LAS tailored for global mobile networks. Our analysis demonstrates that the proposed authentication scheme is secure and delivers enhanced privacy with efficient performance.